EVALUATION OF SURVEY FACTORS ON TRUCK COUNT AND ACHIEVEMENT OF ACTUAL VOLUME OF MINING JULY 2024: EVALUASI SURVEY FACTOR TERHADAP TRUCK COUNT DAN KETERCAPAIAN VOLUME AKTUAL PENAMBANGAN JULI 2024 - Fauzi Syaiful Adam (INTAN Jurnal Penelitian Tambang, 2025)
The planned mining volume (ore and waste) in July 2024 is 417.723,68 bcm delivered from 4 separate mining fronts. Mining operations use CAT 330-GC and Volvo EC 350DL excavators, along with Volvo A40G articulated dump trucks. The ground survey measurements using the Sokkia Atlas GNSS (Global Navigation Satellite System) obtained a total material mined in July 2024 of 271,100 bcm with a survey factor of 106% acquired from the truck count. In the July 2024 mining volume achievement, the physical availability parameter contributed positively as it achieved an increase of 4,226 bcm, however the use of availability and productivity parameters adversely contributed resulting in reduction of54,792 bcm and 96,058 bcm respectively. Factors that led to non-achievement of mining volume in July 2024 were lack of actual productivity per hour, ADT standby due to full stockyard and ADT standby waiting for instructions as the ore material were frequentily in wet condition in the Qatar Front area.